A Lumped Dynamic Modelling Approach for Model-Based Control and Diagnosis of Solid Oxide Fuel Cell System with Anode Off-Gas Recycling. (2nd June 2015) - Marra, Dario; Sorrentino, Marco; Pohjoranta, Antti; Pianese, Cesare; Kiviaho, Jari
Abstract : This work focuses on the identification and validation of a Solid Oxide Fuel Cell (SOFC) stack model that accounts for anode off-gas recycling (AOGR) inclusion. A lumped dynamic modelling approach is adopted to simulate temperature and gas composition at the stack anode outlet. The model is able to simulate the dynamic response of the stack during transients. Experimental data from a real SOFC system are used in model validation and the modeling approach adopted here ensures achieving a satisfactory compromise between estimation accuracy and computational burden. These factors support using the model as state estimator in model-based control and diagnosis algorithms.